2017
DOI: 10.1055/s-0036-1591855
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis of Fused Tetrahydroazocines from Acenaphthylene-1,2-dione, Proline, and Acetylenic Esters

Abstract: A synthesis of dialkyl (12E,14E)-7-oxo-10,11-dihydro-7H,9H-azocino[2,1-a]benzo[de]isoquinoline-13,14-dicarboxylates through a 1,3-dipolar cycloaddition reaction of azomethine ylides, generated in situ from proline and acenaphthylene-1,2-dione, with dialkyl acetylenedicarboxylates is described. According to the X-ray diffraction data, the tetrahydroazocine ring has a rigid twist-boat form with approximate local C2 symmetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…After work up, instead of formation of the desired seven-membered spirooxindole, the chain product 2-(oxoindolin-3-ylidene)­propylidene)­pyrrolidin-1-yl)­acrylate ( 1a ) was obtained in 78% yield. The formation of chain product 1a showed that two molecules of methyl propiolate took part in the reaction and that methyl propiolate played a different role in the reaction than dimethyl acetylenedicarboxylate. A literature survey indicated that 2-(oxoindolin-3-ylidene)­propylidene)­pyrrolidin-1-yl)­acrylate was prepared from various reactions of methyl propiolate for the first time. Thus, the scope of this reaction was examined by using various N -alkylisatins.…”
Section: Resultsmentioning
confidence: 99%
“…After work up, instead of formation of the desired seven-membered spirooxindole, the chain product 2-(oxoindolin-3-ylidene)­propylidene)­pyrrolidin-1-yl)­acrylate ( 1a ) was obtained in 78% yield. The formation of chain product 1a showed that two molecules of methyl propiolate took part in the reaction and that methyl propiolate played a different role in the reaction than dimethyl acetylenedicarboxylate. A literature survey indicated that 2-(oxoindolin-3-ylidene)­propylidene)­pyrrolidin-1-yl)­acrylate was prepared from various reactions of methyl propiolate for the first time. Thus, the scope of this reaction was examined by using various N -alkylisatins.…”
Section: Resultsmentioning
confidence: 99%
“…Next, the 1,3-dipolar cycloaddition was carried out between the azomethine ylide and the dialkyl acetylenedicarboxylate to produce dialkyl (12E,14E)-7-oxo-10,11-dihydro-7H,9H-azocino[2,1a]benzo[de]isoquinoline-13,14-dicarboxylates in yields of 67-83%. 95 In 2018, Yavari and co-workers described a simple route for the synthesis of new perinaphthenones from the reactions of acetylenic esters and acenaphthoquinone-malononitrile adducts by employing a catalytic amount of PPh 3 in CH 2 Cl 2 at 0-25 °C (Scheme 90). Initially, PPh 3 adds to the acetylenic ester to give a Tebby zwitterion.…”
Section: Scheme 88 Synthesis Of New Derivatives Of Phenanthridinesmentioning
confidence: 99%
“…Yavari et al. described a multicomponent method to synthesize eight‐membered azaheterocycles, namely dialkyl(12 E ,14 E )‐7‐oxo‐10,11‐dihydro‐7 H ,9 H‐ azocino[2,1‐ a ]benzo[ de ]isoquinoline‐13,14‐dicarboxylates 390 through a 1,3‐dipolar cycloaddition reaction of dialkyl acetylenedicarboxylates 330 with in situ generated azomethine ylides from the reaction of prolines ( 205 and 218 ) and acenaphthylene‐1,2‐dione 389 (Scheme ) …”
Section: Decarboxylative Reactions Via Azomethine Ylides Pathwaymentioning
confidence: 99%